Emotions Conveyed with New Elegance to Build A Better Boss - Kanniga, E. (International Journal of Psychosocial Rehabilitation, 2019)
The article is written in simple strategic analysis but gives the technical view of various parts of components of brain computer Interface. The works have looked at manufacturing as cost, not as a core capability. Power of one “sixth sense”. Aggregated over time, status updates on social survey give rich insights in to a person’s life says “Clive Thompson" author of smarter than you think, how technology is changing our minds for the better describes the value of internet-enabled public thinking.